CLASSROOM MANAGEMENT CHALLENGES FOR THE PRE SERVICE TEACHER IN TEACHING ENGLISH SPEAKING: (A Case Study the Pre-Service Teacher in 10th Grade at High School in Bandung) - Gantini, Anti (2016)
This study is aimed to investigate classroom management challenges in teaching English speaking faced by the pre-service teacher. This was a descriptive case study using qualitative method as an approach. Classroom observations and interviews were conducted with a pre-service teacher to seek his responses relating to the challenges he faced, and the strategies he gave for improvement of classroom management. The results indicated that the pre-service teacher faced six challenges in managing classroom in teaching English speaking. The challenges were from students' low participation, students' speaking English skill, disrespectful attitude towards pre-service teacher, the limited amount of time, students' motivation and teacher's motivation and expectation. It was also found pre-service teacher's strategies to overcome those challenges. The strategies used by a pre-service teacher to overcome those challenges were making group activities to improve students' participation. Then, a pre-service teacher also makes fun activities to gain the students' attention during lessons, giving rewards for the good behavior, punishment for the wrong deeds, skipping some step and also sharing with the mentor teacher and creates a friendly atmosphere in the class to make students feel recognized and valued to encouraging their motivation. Keywords: Classroom management, preservice teacher, teaching Speaking. Skripsi ini bertujuan untuk menginvestigasi tantangan atau kesulitan manajemen kelas yang dihadapi oleh guru PPL dalam mengajar kemampuan berbicara bahasa Inggris. Skripsi ini merupakan penelitian deskripsi yang menggunakan pendekatan kualitatif. Observasi kelas dan wawancara dilakukan dengan seorang guru PPL untuk mencari jawaban atau respon yang berhubungan dengan tantangan atau kesulitan, dan juga strategi yang digunakan untuk memperbaiki tantangan manajemen kelas yang dihadapi. Hasil dari penelitian ini menunjukan bahwa guru PPL menghadapi enam tantangan dalam mengatur kelas dalam mengajar kemampuan berbicara bahasa Inggris. Tantangan atau kesulitan tersebut adalah kurangnya pastisipasi siswa, kemempuan berbicara bahasa Inggris siswa, sikap tidak menghormati terhadap guru PPL, keterbatasan waktu, motivasi siswa, dan juga motivasi dan ekspektasi guru. Dalam penelitian ini ditemukan juga strategi yang digunakan oleh guru PPL dalam menghadapi tantangan tersebut, diantaranya membuat aktivitas kelompok untuk meningkatkan partisipasi siswa. Kemudian, guru PPL juga membuat aktivitas yang menyenangkan untuk menarik perhatian siswa selama pembelajaran, memberikan hadiah untu setiap perilaku yang baik, hukuman untuk perilaku yang tidak baik, melewati beberapa tahap mengajar dan juga berbagi cerita dan pengalaman dengan guru pamong dan menciptakan lingkungan yang ramah di kelas agar siswa merasa nyaman dan dihargai untuk meningkatkan motivasi mereka. Kata kunci: Manajemen kelas, guru PPL, mengajar kemampuan bahasa Inggris.